Linking the English Cancer Patient Experience Survey to Cancer registration: relating patient experience to outcomes, a step towards better services and outcomes. (2017) - Carneiro, Isabella Gomes; Charnock, James; Fry, Anna; Mak, Vivian; Ormiston-Smith, Nick; McConnell, Hannah; Lyratzopoulos, Yoryos
No abstract available